2004
DOI: 10.1111/j.1365-2567.2004.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient scavenger receptor‐mediated uptake and cross‐presentation of negatively charged soluble antigens by dendritic cells

Abstract: SUMMARYExogenous antigens endocytosed in large amounts by antigen-presenting cells (APC) are presented on major histocompatibility complex (MHC) class I molecules as well as on class II molecules, a process called cross-presentation. Among APC, dendritic cells (DC) play a key role in cross-presentation by transporting internalized antigen to the cytosol. The present study shows that ovalbumin (OVA) introduced with negative charges by succinylation (Suc-OVA), maleylation (Mal-OVA) or cis-aconitylation (Aco-OVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 40 publications
3
25
1
2
Order By: Relevance
“…In vitro assays confirmed that the absence of receptors did not affect AM binding of OVA, as doubledeficient AMs bound Alexa-OVA to nearly the same extent as did control AMs (data not shown). These findings are consistent with previous reports indicating that, unlike chemically modified albumin, native albumin binding to MΦs is not mediated through SRAs (17)(18)(19), and also indicate that nebulization does not per se denature the allergenic proteins sufficiently to create SRA-binding domains.…”
Section: Wt and Sra-deficient Lung Mφs Show Normal Uptake Of Inhaled supporting
confidence: 82%
See 2 more Smart Citations
“…In vitro assays confirmed that the absence of receptors did not affect AM binding of OVA, as doubledeficient AMs bound Alexa-OVA to nearly the same extent as did control AMs (data not shown). These findings are consistent with previous reports indicating that, unlike chemically modified albumin, native albumin binding to MΦs is not mediated through SRAs (17)(18)(19), and also indicate that nebulization does not per se denature the allergenic proteins sufficiently to create SRA-binding domains.…”
Section: Wt and Sra-deficient Lung Mφs Show Normal Uptake Of Inhaled supporting
confidence: 82%
“…The context for our findings includes the recognition of the important role of dendritic cells (DC) in the pathogenesis of asthma (21), and as professional antigen-presenting cells which bridge innate and adaptive immunity (22,23). DCs express SR-AI/II, which functions in antigen presentation and adaptive immunity (17,19,(24)(25)(26)(27)(28). For example, SR-AI/II -/-mice are deficient in mounting an efficient T cell response to maleylated murine serum albumin, a known SR-AI/II ligand (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMs can efficiently bind and internalize unopsonized particles and bacteria through SR-As, leading to the clearance of inhaled matter from the airways and the reduction of the resulting inflammation (7)(8)(9) and are known to similarly bind modified proteins (17)(18)(19). To determine whether SR-As could reduce allergic inflammation by simply "scavenging" aeroallergen with a resulting decrease in allergen dose, we measured their ability to internalize inhaled allergens using FITC-OVA.…”
Section: Wt and Sr-a-deficient Lung M⌽s Show Normal Uptake Of Inhaledmentioning
confidence: 99%
“…S3D), indicating that ubiquitination of the MR indeed is important for cross-presentation. In addition, the moderate cross-presentation efficiency of control cells indicates the existence of alternative pathways in these cells, which has already been observed by others (19,20). Subsequently, we investigated whether reduced cross-presentation was due to an impaired antigen transport into the cytoplasm.…”
Section: Mr Ismentioning
confidence: 99%